Myeloid-Derived Suppressor Cells in Immune Microenvironment Promote Progression of Esophagogastric Junction Adenocarcinoma - Wang, Ying; Sun, Haiyan; Zhu, Ningning; Wu, Xianxian; Sui, Zhilin; Gong, Lei; Yu, Zhentao (Frontiers in Oncology, 2021)
Adenocarcinoma of the esophagogastric junction (AEG) is a fatal disease. Accumulating evidence indicates that, for a comprehensive understanding of AEG, studies should be conducted not only to investigate tumor cells, but also the tumor microenvironment (TME). In this study, we collected AEG patient data from The Cancer Genome Atlas, and used the CIBERSORT algorithm to analyze tumor-infiltrating immune cell profiles. The levels of CD8+ T cells and M0 and M2 macrophages were relatively high in AEG tissues. M2 macrophages were abundant in G3 tumors, and neutrophils were associated with poor prognosis. Myeloid-derived suppressor cells (MDSCs) represent a heterogeneous population of immunosuppressive cells which share a similar origin to neutrophils and macrophages. We further analyzed the levels of MDSCs in AEG patients and healthy donors (HD) using flow cytometry. MDSC levels were elevated at tumor sites, with polymorphonuclear MDSCs (PMN-MDSCs) being the predominant subtype. Circulating MDSCs partly represented cells at the tumor site. We observed that PMN-MDSC levels at tumor sites were positively correlated with advanced staging, low grade, lymph node metastasis, and HER2- status. Immunohistochemistry and immunofluorescence analyses indicated that activation of the STAT3 and NF-κB pathways in MDSCs may be a potential mechanism for cancer progression. Our studies provided a comprehensive perspective involving tumor-infiltrating immune cells, and detailed insights into the proportion of MDSCs in AEG and their clinical significance. Together, these findings may improve our current understanding of cancer progression involving tumor-infiltrating immune cells in the TME.